Case Report: An unclassified T cell lymphoma subtype with co-expression of TCR αβ and γ chains revealed by single cell sequencing - Song, Wei; Wang, Gang; Wang, Cheng; Liu, Lulu; Zhang, Liming; Zhang, Ruoyu; Zhang, Haixi; Shi, Keqian (Frontiers in Immunology, 2023)
Background T cell lymphomas (TCL) are a group of heterogeneous diseases with over 40 subtypes. In this study, we identified a novel TCL subtype which was featured by a unique T cell receptor (TCR) presentation, α, β and γ chains were co-existing in a single malignant T cell. Case presentation A 45-year-old male patient was diagnosed T cell lymphoma after 2-month of abdominal distension and liver enlargement. Combining histology review, PET-CT scanning and immunophenotyes, the patient was not classified to any existing TCL subtypes. To better understand this unclassified TCL case, we performed single cell RNA sequencing paired with TCR sequencing on the patient’s PBMC and bone marrow samples. To our surprise, we identified that the malignant T cells had a very rare TCR combination, by expressing two α chains, one β chain and one γ chain simultaneously. We further studied the molecular pathogenesis and tumor cell heterogeneity of this rare TCL subtype. A set of potential therapeutic targets were identified from the transcriptome data, such as CCL5, KLRG1 and CD38. Conclusions We identified the first TCL case co-expressing α, β and γ chains and dissected its molecular pathogenesis, providing valuable information for precision medicine options for this novel TCL subtype.